The role of Bh4 in parallel evolution of hull colour in domesticated and weedy rice. (17th July 2013) - Vigueira, C. C.; Li, W.; Olsen, K. M.
Abstract: The two independent domestication events in the genus Oryza that led to African and Asian rice offer an extremely useful system for studying the genetic basis of parallel evolution. This system is also characterized by parallel de‐domestication events, with two genetically distinct weedy rice biotypes in the US derived from the Asian domesticate. One important trait that has been altered by rice domestication and de‐domestication is hull colour. The wild progenitors of the two cultivated rice species have predominantly black‐coloured hulls, as does one of the two U.S. weed biotypes; both cultivated species and one of the US weedy biotypes are characterized by straw‐coloured hulls. Using Black hull 4 ( Bh4 ) as a hull colour candidate gene, we examined DNA sequence variation at this locus to study the parallel evolution of hull colour variation in the domesticated and weedy rice system. We find that independent Bh4‐ coding mutations have arisen in African and Asian rice that are correlated with the straw hull phenotype, suggesting that the same gene is responsible for parallel trait evolution. For the U.S. weeds, Bh4 haplotype sequences support current hypotheses on the phylogenetic relationship between the two biotypes and domesticated Asian rice; straw hull weeds are most similar to indica crops, and black hull weeds are most similar to aus crops. Tests for selection indicate that Asian crops and straw hull weeds deviate from neutrality at this gene, suggesting possible selection on Bh4 during both rice domestication and de‐domestication.